Chinese Identity in God Temple's Birthday Ceremony as a Form of Social Network - Celerina Dewi Hartati; Gustini Wijayanti; Hin Goan Gunawan; Yulie Neila Chandra (Cakrawala - Jurnal Humaniora, 2020)
This study aims to show a form of Chinese social network in the form of a god’s temple birthdayceremony. This ceremony shows a form of social group identity as Chinese people in which shows a concept ofsocial networks. This research is ethnographic research, with the case of a god’s temple birthday ceremony. Dataobtained through interviews with the temple administrator, and observations during the preparation and the dayof the god's temple birthday ceremony. The result is the god’s temple's birthday ceremony is a tradition that ismaintained by the Chinese so as not to disappear and become an identity as a Chinese. The tradition istransmitted from time to time from one place to another place through a social network. This social networkwhich is formed comes from a network between the temples as an institution that has the same main god.Ceremony as a tradition is taught from generation to generation, demonstrated, and trusted. The ceremony washeld in order to maintain a relationship with the past with the ancestors and preserve the social group identity.